Short-Term Thermal Acclimation Modifies the Metabolic Condition of the Coral Holobiont - Gibbin, Emma M.; Krueger, Thomas; Putnam, Hollie M.; Barott, Katie L.; Bodin, Julia; Gates, Ruth D.; Meibom, Anders (Frontiers in Marine Science, 2018)
The nutritional symbiosis between coral hosts and photosynthetic dinoflagellates is fundamental to the functioning of coral reefs. Rising seawater temperatures destabilize this relationship, resulting in drastic declines in world-wide coral cover. Thermal history is thought to play an important role in shaping a coral’s response to subsequent thermal stress. Here, we exposed Pocillopora damicornis to two thermal acclimation regimes (ambient vs. warm) and compared the effect that acclimation had on the coral holobiont’s response to a subsequent seven day heat stress event. We conducted daily physiological measurements at the holobiont level (gross photosynthesis, respiration, host protein content, symbiont density and chlorophyll content) throughout the heat stress event, as well as cellular-level imaging of 13C-bicarbonate and 15N-nitrate assimilation using NanoSIMS, at the end of the heat stress event. Thermal acclimation history had a negligible effect on the measurements conducted at the holobiont level during the heat event. No differences were observed in the O2-budget between ambient and warm-acclimated corals and only small fluctuations in host protein, symbiont density and chlorophyll content were detected. In contrast, this lack of differential response, was not mirrored at the cellular level. Warm-acclimated corals had substantially higher 13C enrichment in the host gastrodermis and lipid bodies, but significant lower 15N-nitrate assimilation in the symbionts and the host tissue layers, relative to the ambient-acclimated corals. We discuss potential reasons for the disconnect that occurred between symbiont bicarbonate and nitrate assimilation (in the absence of photosynthetic breakdown) in the warm-acclimated corals. We suggest this represents either a shift in nitrogen utilisation, or supply limitation by the host. Our findings raise several interesting hypotheses regarding the role that nitrogen metabolism plays in thermal stress, which will warrant further investigation if we are to understand the acclimatisation capacity of the coral holobiont.